Atividade antimicrobiana e toxicidade in vitro e in vivo de extratos de Equisetum hyemale - de Queiroz, Geisiany Maria [UNESP]; de Souza-Moreira, Tatiana Maria [UNESP]; Salgado, Hérida R. N. [UNESP]; Moreira, Raquel Regina Duarte [UNESP]; Utrera, Susane Hellen; Martins, Carlos Henrique Gomes; Linhari Rodrigues Pietro, Rosemeire C. [UNESP] (My University, 2014)
Equisetum hyemale L. (Equisetaceae) species is considered a medicinal plant used in the form of teas to combat infectious or inflammation diseases, presenting several compounds related to these actions. There are no extensive studies about the use against different microbial groups as well as for the toxicity. The objective of these studies was for the first time evaluated the antimicrobial activity against oral microorganisms and the in vitro and in vivo toxicity of 70% ethanol and methanol E. hyemale extracts. Antimicrobial activity assays were performed by broth microdilution technique to determine the Minimum Inhibitory Concentration (MIC) and the cytoxicity was assayed in vitro and acute toxicity in vivo was performed with mice. The methanol extracts, showed better antimicrobial activity against oral microorganisms whit MIC of 0.5 mg/mL. Both extracts presented low cytotoxicity even in high concentrations and the 70% ethanol extract of E. hyemale did not present toxicity inducing significant alterations and/or death in mice. This results suggests that both extracts exhibits great potential to therapeutic applications.
Antimicrobial activity and toxicity in vitro and in vivo of Equisetum hyemale extracts
Keywords: Equisetum hyemale; Extracts; Oral microorganisms; Toxicity